O-antigen biosynthesis gene clusters of Escherichia albertii: their diversity and similarity to Escherichia coli gene clusters and the development of an O-genotyping method. Issue 11 (18th November 2019) - Ooka, Tadasuke; Seto, Kazuko; Ogura, Yoshitoshi; Nakamura, Keiji; Iguchi, Atsushi; Gotoh, Yasuhiro; Honda, Mikiko; Etoh, Yoshiki; Ikeda, Tetsuya; Sugitani, Wakana; Konno, Takayuki; Kawano, Kimiko; et al.
Abstract : Escherichia albertii is a recently recognized human enteropathogen that is closely related to Escherichia coli . In many Gram-negative bacteria, including E. coli, O-antigen variation has long been used for the serotyping of strains. In E. albertii, while eight O-serotypes unique to this species have been identified, some strains have been shown to exhibit genetic or serological similarity to known E. coli / Shigella O-serotypes. However, the diversity of O-serotypes and O-antigen biosynthesis gene clusters (O-AGCs) of E. albertii remains to be systematically investigated. Here, we analysed the O-AGCs of 65 E. albertii strains and identified 40 E. albertii O-genotypes (EAOgs) (named EAOg1–EAOg40). Analyses of the 40 EAOgs revealed that as many as 20 EAOgs exhibited significant genetic and serological similarity to the O-AGCs of known E. coli / Shigella O-serotypes, and provided evidence for the inter-species horizontal gene transfer of O-AGCs between E. albertii and E. coli . Based on the sequence variation in the wzx gene among the 40 EAOgs, we developed a multiplex PCR-based O-genotyping system for E. albertii (EAO-genotyping PCR) and verified its usefulness by genotyping 278 E. albertii strains from various sources. Although 225 (80.9 %) of the 278 strains could be genotyped, 51 were not assigned to any of the 40 EAOgs, indicating that further analyses are required to better understand the diversity of O-AGCs in E. albertii and improve the EAO-genotyping PCR method. A phylogenetic view of E. albertii strains sequenced so far is also presented with the distribution of the 40 EAOgs, which provided multiple examples for the intra-species horizontal transfer of O-AGCs in E. albertii .